Static and Dynamic Buckling of Rectangular Functionally Graded Plates Subjected to Thermal Loading - Czechowski, L.; Kowal-Michalska, K. (Проблемы прочности, 2013)
In the paper, the buckling phenomenon for static
and dynamic loading (pulse of finite duration)
of functionally graded plates subjected to uniform
temperature increment is presented. The
work deals with thin rectangular plates with unmovable
edges, simply supported or clamped
along all edges. The material properties varying
smoothly across the thickness are assumed to be
temperature-independent. The investigations are
conducted for different values of volume fraction
index and uniform temperature rise in form
of rectangular pulse of finite duration. Представлено явление потери устойчивости при статической и динамической нагрузке
(импульс конечной длительности) функционально-градиентных пластин, подверженных воздействию равномерного повышения температуры. Рассмотрены шарнирно опертые или
закрепленные (вдоль кромок) тонкие прямоугольные пластины с неподвижными кромками.
Предполагается, что свойства материала, плавно изменяющиеся по толщине, не зависят от
температуры. Проведены исследования для разных значений коэффициента относительного
объема и равномерного приращения температуры, представленного в виде прямоугольного
импульса конечной длительности. Представлено явище втрати стійкості під час статичного і динамічного навантаження (імпульс скінченної тривалості) функціонально-градієнтних пластин
за рівномірного підвищення температури. Розглянуто шарнірно оперті або
закріплені (вздовж кромок) тонкі прямокутні пластини з нерухомими кромками. Припускається, що властивості матеріалу, які плавно змінюються по
товщині, не залежать від температури. Проведено дослідження для різних

значень коефіцієнта відносного об’єму і рівномірного приросту температури,
представленого у вигляді прямокутного імпульсу скінченної тривалості.